Plasma sodium measurements by direct ion selective methods in laboratory and point of care may not be clinically interchangeable. - Weld, Brigit; Morgan, Thomas; Presneill, Jeffrey; Weier, Steven; Cowley, David; Weld, Brigit A; Morgan, Thomas J; Presneill, Jeffrey J (Journal of Clinical Monitoring & Computing, 2017)
An estimated 25 % of indirect ion selective electrode (ISE) ICU plasma sodium measurements differ from corresponding direct ISE values by at least 4 mmol/L, the dominant factor being indirect ISE over-estimation driven by hypoproteinemia. Since direct measurements are considered unaffected by protein concentrations, we investigated whether direct ISE plasma sodium measurements in the laboratory and at point of care in ICU show sufficient agreement to be clinically interchangeable. From a 5 year clinical chemistry database, 9910 ICU plasma samples were assessed for agreement between direct ISE sodium measurements in ICU (ABL 700) and in the central laboratory (Vitros Fusion). The relationship between differences in paired plasma sodium measurements (Vitros-ABL) and total plasma protein concentrations was evaluated by generalized estimating equation linear regression. Patients were hypo-proteinemic [mean (SD) total protein concentration 56.9 (9.04) g/L]. Mean (SD) paired Vitros-ABL sodium measurements was -0.087 (1.74) mmol/L, range -14 to +10 mmol/L. Disagreement at ≥|4|mmol/L, ≥|3|mmol/L and ≥|2|mmol/L was present in 409 (4.1 %), 1333 (13.4 %) and 3591 (36.2 %) pairs respectively. Test-retest disagreement estimates within either source alone were substantially lower. Small negative Vitros-ABL differences associated with low plasma protein concentrations were reversed at high protein concentrations. Disagreement between plasma sodium concentrations monitored by two common direct ISE analyzers was substantially less than reported between direct and indirect ISE devices, although a protein influence of low clinical importance persisted. Disagreement was sufficient to jeopardize safe interchangeable interpretation in situations with a low tolerance for imprecision, such as hyponatremia correction.